Option contracts in fresh produce supply chain with circulation loss - Chong Wang; Xu Chen (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The purpose of this paper is to investigate management decisions via option contracts in a two-stage supply chain in which a fresh produce supplier sells to a retailer, considering the circulation loss of the fresh produce. Design/methodology/approach: Authors propose a Stackelberg model to analyze the supply chain members' decisions in the decentralized supply chain compared with the integrated one under the newsvendor framework. Findings: The results illustrate that there exists a unique optimal option order quantity for the retailer and a unique optimal option order price for the supplier giving certain conditions; furthermore, option contracts cannot coordinate the fresh produce supply chain when the retailer only orders options. Originality/value: Agricultural products especially fresh produce's characteristics such as circulation loss and high risk are considered. Option contracts and game theory are combined to manage the fresh produce supply chain's risk. The proposed tool and models are hoped to shed light to the future works in the field of supply chain risk management.
Keywords: 650; fresh produce; supply chain; option contracts; management decisions